Kicking the can down the road? Educational solutions to the challenges of divided societies: a Northern Ireland case study. Issue 2 (4th March 2021) - Roulston, Stephen; Hansson, Ulf
ABSTRACT: There is considerable literature concerning the impact of education in divided societies. Some seek to defend separate schools, often for different faith groups, while others stress the benefits of school integration on social cohesiveness. Contact theory has been employed in efforts in many countries to address social discord. Northern Ireland is a deeply divided multicultural society with a largely separate system of education for its two main communities. There is also a small but growing Integrated schools sector, where the communities learn together and where contact is maintained. A more recent intervention in Northern Ireland is that of Shared Education where separate schools are retained but shared classes and other opportunities for sharing are offered. This paper examines these models of educational provision and evaluates them in light of political developments. This is of particular importance as the structure of education is key to social cohesion for the people in Northern Ireland, as well as in other jurisdictions across the world contemplating educational solutions for divided societies.